Identidade docente: as várias faces do “ser” professor bacharel - Lima, Andressa Barreto (2023)
In a critical-reflective movement, this research was born, from a perspective in which the life stories of the collaborators reveal a formative identity. The decision to write this dissertation comes from a natural and organic moment, insofar as I deepened the readings about the theme of teaching identity in university teaching. The objective is to understand the process of constitution of the teaching identity of bachelor teachers who work in higher education in Health Sciences courses. The methodology of this research, in a perspective, of (auto)biographical narratives that can reveal formative identities. The procedures for producing information are divided into two stages: a narrative interview and a conversation with bachelors in Health. The construction of the teacher's identity requires a broad knowledge and analysis of the knowledge and practice that permeate their activities and experiences. Among the theoretical bases that contributed to the development of the study, the authors who discuss professionalization and experience stand out, PIMENTA (2002), MAURICE TARDIF (2000, 2002, 2010) and JORGE LARROSA (2002) and in the discussions about teaching identity NÓVOA (1997), GIDDENS (1997), BENDLE (2002), DUBAR (2005), TARDIF (2012), PEPPER AND ANASTASIOU (2018). To conclude that we start from the assumption, from a central nucleus, that when narrating their formative life story, the teachers blossomed, in the face of the subjectivity of their being, starting from a subjective time and space of them, revealing the individual meanings arising from childhood, family and friends, mobilizing meanings and senses.